Implementation Of Training Needs Assessment Of Employees Of The Office Of The Regency Of Gowa Regency - Candra Kirana (Pustaka Digital Indonesia, 2021)
This study aims to find out and explain how the model for implementing the Training Needs Assessment for Gowa Regent Office employees is. This research was conducted at the Gowa Regent's Office, BKPSDM Section. The sample in this study was 6 informants and 200 employees who had attended training at the Gowa Regent's office. The technique used is direct interview. Analysis of the data used is a qualitative analysis which was carried out during data collection and after data collection was completed. This qualitative research data analysis activity was carried out interactively and continued until it was completed through several systematic activity steps, namely data collection, data reduction, data display. The results of this study show that the development of Human Resources through Training Needs Assessment at the Gowa Regent's Office is effective. used in gathering information on training needs at the Gowa Regent's Office.